2010
DOI: 10.1016/j.ejso.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict local recurrence in breast conserving surgery after neoadjuvant chemotherapy?

Abstract: International audienceOne of the benefits of neoadjuvant chemotherapy (NAC) is its ability to convert patients ineligible for breast conservative treatment (BCT) to be candidates for this treatment, although questions have been raised regarding the effectiveness of BCT in terms of loco-regional recurrence (LRR). The objective of this study is to evaluate LRR in this group and the influence of tumor characteristics in recurrence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…In the present study, two types of tumor regression were observed by MRI after NAC for the breast cancer patients . The results showed that 44.3% of tumors had concentric shrinkage while 55.7% were nests/had dendritic shrinkage, which is consistent with the results of Takeda et al .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, two types of tumor regression were observed by MRI after NAC for the breast cancer patients . The results showed that 44.3% of tumors had concentric shrinkage while 55.7% were nests/had dendritic shrinkage, which is consistent with the results of Takeda et al .…”
Section: Discussionsupporting
confidence: 92%
“…Although ipsilateral thoracic wall events involving the sternal bone were defined as a distant event in 2014 31, previous studies with long follow-up period did not specify this form of recurrence 32. In the present study, we observed 2 patients with simultaneous IBTR and sternal infiltration, but 1 patient underwent local full-thickness chest wall resection.…”
Section: Discussionmentioning
confidence: 45%
“…Advanced tumor size at diagnosis was also found to be an independent risk of recurrence by other authors [16,21]. In addition, a trend between LVI and LR was demonstrated but lacked statistical significance [16].…”
Section: Predictors Of Local Recurrencementioning
confidence: 94%
“…He concluded that residual tumor diameter >2 cm after NACT, positive axillary lymph node, multifocal residual disease, and lympho-vascular invasion (LVI) were strongly correlated with risk for LR [23]. Advanced tumor size at diagnosis was also found to be an independent risk of recurrence by other authors [16,21]. In addition, a trend between LVI and LR was demonstrated but lacked statistical significance [16].…”
Section: Predictors Of Local Recurrencementioning
confidence: 94%